Maternal apo E genotype is a modifier of the Smith-Lemli-Opitz syndrome. Issue 8 (30th July 2004) - Witsch-Baumgartner, M; Gruber, M; Kraft, H G; Rossi, M; Clayton, P; Giros, M; Haas, D; Kelley, R I; Krajewska-Walasek, M; Utermann, G
Abstract : Background: Smith-Lemli-Opitz syndrome (MIM 270400) is an autosomal recessive malformation and mental retardation syndrome that ranges in clinical severity from minimal dysmorphism and mild mental retardation to severe congenital anomalies and intrauterine death. Smith-Lemli-Opitz syndrome is caused by mutations in the Δ7 sterol-reductase gene (DHCR7; EC 1.3.1.21), which impair endogenous cholesterol biosynthesis and make the growing embryo dependent on exogenous (maternal) sources of cholesterol. We have investigated whether apolipoprotein E, a major component of the cholesterol transport system in human beings, is a modifier of the clinical severity of Smith-Lemli-Opitz syndrome. Method: Common apo E, DHCR7, and LDLR genotypes were determined in 137 biochemically characterised patients with Smith-Lemli-Opitz syndrome and 59 of their parents. Results: There was a significant correlation between patients' clinical severity scores and maternal apo E genotypes (p = 0.028) but not between severity scores and patients' or paternal apo E genotypes. In line with their effects on serum cholesterol levels, the maternal apo ϵ2 genotypes were associated with a severe Smith-Lemli-Opitz syndrome phenotype, whereas apo E genotypes without the ϵ2 allele were associated with a milder phenotype. The correlation of maternal apo E genotype with disease severity persisted after stratification for DHCR7 genotype. There was no association of Smith-Lemli-Opitz syndrome severity with LDLR gene variation. Conclusions: These results suggest that the efficiency of cholesterol transport from the mother to the embryo is affected by the maternal apo E genotype and extend the role of apo E and its disease associations to modulation of embryonic development and malformations.